2021
DOI: 10.3389/fcosc.2021.657691
|View full text |Cite
|
Sign up to set email alerts
|

Submerged Aquatic Vegetation Patch Size Affects Fish Communities in a Turbid-Algal Lake

Abstract: Submerged aquatic vegetation (SAV) is declining worldwide, leading to subsequent reductions in the ecological functions associated with SAV in shallow aquatic ecosystems, including providing habitat for fishes. Extensive restoration efforts are required to reverse this trend, but studies focusing on aquatic vegetation have been uncommon in recent years relative to other primary producers. Evaluations of the most beneficial SAV species and characteristics for fishes are especially rare. Because of the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Although SAV preference can vary among fish species, it is difficult to recommend one SAV species over another in shallow Florida lakes. Instead, Looby et al (2021) determined that patch size of SAV habitat, not species composition, was the most significant contributing environmental variable to fish community structure and total fish biomass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SAV preference can vary among fish species, it is difficult to recommend one SAV species over another in shallow Florida lakes. Instead, Looby et al (2021) determined that patch size of SAV habitat, not species composition, was the most significant contributing environmental variable to fish community structure and total fish biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Fish and Wildlife Service and U.S. Bureau of the Census 2016). Changes in littoral SAV cover can have major effects on fish species composition and biomass in shallow eutrophic lakes (Rogers and Allen 2008; Looby et al 2021). Understanding locally how Largemouth Bass abundance and recruitment are influenced by SAV coverage is essential for effective fish management practices.…”
Section: Introductionmentioning
confidence: 99%
“…According to Wang et al (2013), total abundance and biomass of the comet fish Carassius auratus are found dominant in lake environments overgrown with aquatic plants. The submerged aquatic plants carry out photosynthesis by utilizing dissolved inorganic carbon (Pedersen et al, 2013;Khairnar & Kaur, 2018), creating healthy environment which may promote high species richness, growth, foraging, and survival of fishes, notably juveniles and smaller individuals, due to optimal spaces for predator-prey interactions and edge effects (Looby et al, 2021). Increased survival rate was positively correlated with the specific growth rate value.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the feed intake value in this study had no significant difference among the treatments. Several previous studies which used aquatic plants had similar specific growth rate that affected the fish life (Ismail et al, 2018;Looby et al, 2021;Aminisarteshnizi, 2022). In contrast, at limited and excessive vegetation may decrease fish growth rates at 75% to 85% of plant community coverage (Ismail et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of vegetation patch dimensions on flow structures has significant consequences for the ecosystem through various mechanisms. For example, an intermediate coverage (10-40%) of vegetation may promote high species richness due to the conditions provided by the optimal behavior of flow [10][11][12]. In addition, flow structures around a vegetation patch have a significant impact on the sediment transport, and consequently on the topography of the river bed [13][14][15].…”
Section: Introductionmentioning
confidence: 99%